2012
DOI: 10.1186/1471-2156-13-34
|View full text |Cite
|
Sign up to set email alerts
|

Gene diversity, agroecological structure and introgression patterns among village chicken populations across North, West and Central Africa

Abstract: BackgroundChickens represent an important animal genetic resource for improving farmers’ income in Africa. The present study provides a comparative analysis of the genetic diversity of village chickens across a subset of African countries. Four hundred seventy-two chickens were sampled in 23 administrative provinces across Cameroon, Benin, Ghana, Côte d’Ivoire, and Morocco. Geographical coordinates were recorded to analyze the relationships between geographic distribution and genetic diversity. Molecular chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 42 publications
(57 reference statements)
2
29
1
Order By: Relevance
“…A study of the same data revealed a greater rate of European introgression in closer proximity to animal markets (Mbole-Kariuki et al, 2014). A study of African village chickens from multiple locations (Leroy et al, 2012) reported evidence of introgression in some of the countries, including Morocco and Cameroon, whereas finding negligible gene flow in some other countries such as Benin or Ghana.…”
Section: Evidence Of Crossbreeding In Developing Countriesmentioning
confidence: 97%
See 1 more Smart Citation
“…A study of the same data revealed a greater rate of European introgression in closer proximity to animal markets (Mbole-Kariuki et al, 2014). A study of African village chickens from multiple locations (Leroy et al, 2012) reported evidence of introgression in some of the countries, including Morocco and Cameroon, whereas finding negligible gene flow in some other countries such as Benin or Ghana.…”
Section: Evidence Of Crossbreeding In Developing Countriesmentioning
confidence: 97%
“…However, in developing countries, pedigree and performance recording remain a bottleneck for the implementation of selection schemes . More generally, genomics provides effective tools to assess and monitor the level of introgression within local population (Leroy et al, 2012;Murray et al, 2013). Genome-wide analysis of crossbred and improved livestock under tropical conditions may also reveal the genomic regions submitted to recent selection and therefore linked to adaptation, as investigated by Kim and Rothschild (2014) in Kenyan dairy cattle.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, free-range scavenging village chickens (Dessie et al, 2011;Leroy et al 2012;Desta et al, 2013) also offer large potential to understand the genetic control of phenotypic diversity. Since village chickens possess a richness of accumulated recombination and a number of adaptive characteristics for extreme environments such as high temperature, they provide a useful genetic resource for high-resolution genetic mapping (Wragg et al, 2012;Megens and Groenen, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A combination of SSR and mtDNA markers is a complementary approach that combines the highly polymorphic microsatellites whose high mutation rates allow for small scale resolution of more recent demographic event with mtDNA which shed light on phylogeographic events dating back further in time (Feulner et al, 2004). Microsatellites have been used to asses genetic diversity of a number of native chicken population in Africa (Leroy et al, 2012;Goraga et al, 2012;Eltanany et al, 2011), Europe Wilkinson et al, 2012;Zanetti et al, 2011;Bodzsar et al, 2009) and Asia (Pham et al, 2013;Cuc et al, 2010;Berthouly et al, 2009;Ngo Thim et al, 2006). The first chicken genome sequence draft was completed in 2004 (International Chicken Consortium, 2004); its availability offers new opportunities in the evaluation of chicken genetic diversity using SNPs (Gholami et al, 2014;Granevitze et al, 2014;Siwek et al, 2013;Groenen et al, 2009;Muir et al, 2008).…”
Section: Introductionmentioning
confidence: 99%